A comparative analysis of the implementation of public-private partnership (PPP) in the Palapa Ring project: Case study of western, central, and eastern packages - Ikhsanti, Putri Maziya; Arnezti, Nicky; Alika, Denisya Ziva (Economic Military and Geographically Business Review, 2025)
Background: The Palapa Ring project, as one of the largest telecommunications infrastructure initiatives in Indonesia, uses a Public Private Partnership (PPP) scheme to support the construction of a national fiber optic network in 57 districts/cities in order to build internet accessibility, especially in the 3T area which is divided into western, central and east packages. However, there are differences in the implementation of the three packages. This research aims to analyze the comparison, the use of funds, and challenges. Methods: This research uses a qualitative descriptive approach with a literature study method and uses secondary data from various relevant sources. Findings: The impact of implementing this project shows that it has generally had a positive impact. The Eastern region has a more unequal average change in internet users while the west is more evenly distributed and more developed. Among the three packages, the Central region has a higher growth rate among the three packages. The Use of Funds shows that the Western Package has the highest efficiency with a utilization of 69% while the Central Package and Eastern Package are lower at 37.67% and 37.38% respectively due to significant geographical and operational challenges. The Availability Payment (AP) scheme supports the sustainability of the project. Conclusion: In conclusion, the Palapa Ring project positively impacts internet access, but regional differences in user growth and fund efficiency highlight the Western package as the most efficient compared to the more challenged Central and Eastern packages. Novelty/Originality of this article: This research recommends optimizing network utilization and operational cost efficiency to support the success of digital transformation in Indonesia.